Pengukuran Kesinambungan Fiskal di Indonesia - Widiastuti, Nur; Fitrady, Ardyanto; Widodo, Tri (Jurnal Ekonomi & Kebijakan Publik, 2024)
Fiscal sustainability has become a concern in many economies due to increasing government debt trends, including in Indonesia. The results of existing research on fiscal sustainability show no uniformity in measurement indicators and provisions for the government debt threshold. This study aims to measure the fiscal sustainability threshold in Indonesia. This research was conducted using time series data during the 2000 – 2019 period and applied four measurement methods: the standard method, the Operational Recursive Algorithm, the probabilistic method, and the sudden stop of modal flow in Indonesia.The measurement results show that fiscal policy in Indonesia is not sustainable based on the standard method of fiscal policy during the period 2000 - 2019. However, the Operational Recursive Algorithm method results show that fiscal policy in Indonesia is sustainable. The Probabilistic approach estimates that the safe ratio of government debt is 69.69%, concluding that Indonesia's fiscal sector is sustainable. The Sudden Stop approach shows that in 2005 – 2014, 2016, and 2019, the value of β is larger than 1. This value means that the position of government debt is dominated by debt in domestic currency units, tradable goods dominate national income, and fiscal sustainability is influenced more by changes in the internal environment. In 2015 and 2017 – 2019, however, the value of β is lower than 1. This shift is due to an increase in debt denominated in domestic currency followed by a decrease in the composition of tradable goods. The overall conclusion from the analysis using the four methods is that fiscal policy in Indonesia is a sustainable policy. AbstrakKesinambungan fiskal menjadi perhatian di banyak perekonomian, terutama dengan adanya tren peningkatan jumlah utang pemerintah di banyak negara, termasuk di Indonesia. Hasil penelitian yang ada tentang kesinambungan fiskal menunjukkan ketidakseragaman dalam hal indikator pengukuran maupun ketentuan ambang batas utang pemerintah. Penelitian ini bertujuan mengukur ambang batas kesinambungan fiskal di Indonesia, dengan mengaplikasikan empat metode pengukuran, yaitu: metode standar, operational recursive algorithm, probabilistic dan sudden stop aliran modal. Penelitian ini menggunakan data sekunder berbentuk kurun waktu selama periode tahun 2000 sampai dengan 2019. Hasil pengukuran menunjukkan bahwa berdasarkan metode standar kebijakan fiskal selama periode tahun 2000 - 2019 tidak berkesinambungan. Namun hasil metode Operasional Recursive Algorithm menunjukkan kebijakan fiskal di Indonesia merupakan kebijakan yang berkesinambungan. Estimasi pendekatan Probabilistic menunjukkan bahwa rasio utang pemerintah yang aman adalah 69,69% sehingga fiskal di Indonesia berkesinambungan. Pendekatan Sudden Stop menunjukkan bahwa pada 2005 – 2014, 2016, dan 2019 besarnya  lebih besar dari 1. Hal ini menunjukkan posisi utang pemerintah didominasi oleh utang dalam satuan mata uang domestik, pendapatan nasional didominasi oleh tradable goods, dan kesinambungan fiskal lebih dipengaruhi perubahan lingkungan internal. Pada tahun 2015, 2017 – 2019 nilai  lebih kecil dari 1. Kesimpulan akhir dari analisis dengan keempat metode tersebut adalah bahwa kebijakan fiskal di Indonesia adalah kebijakan yang berkesinambungan.